Problem-Based Learning Model Assisted with A Humanistic-Merdeka Belajar Approach Improved Biology Students’ Learning Ownership - Mulyani, Dita Tri; Listyorini, Dwi; Sari, Murni Sapta (Jurnal Pendidikan Sains, 2024)
Fostering ownership over learning constitutes a pivotal aspect for students to cultivate a comprehensive understanding, employ cognitive strategies effectively, hone essential skills, and refine learning methodologies. Preliminary studies have underscored a prevalent deficiency in the learning ownership among biology students, categorizing it as notably low. The purpose of this study is to ascertain the effect of the Project Based Learning (PBL) model assisted with a Humanistic-Merdeka Belajar (HMB) approach, in nurturing students’ ownership of their learning endeavors. Employing a quasi-experimental design, the research adopts a pre-test post-test non-equivalent control group configuration, administered both prior to and following the intervention within each respective group. Data collection entails pre-test and post-test evaluations conducted through structured questionnaires. Subsequent data analysis involves employing one-way ANOVA and LSD post hoc tests. The findings distinctly indicate a positive and statistically significant impact of the HMB approach on students’ learning ownership. Moreover, notable disparities in learning ownership emerge between the groups utilizing the PBL-HMB, PBL, and presentations-assignment approaches. Consequently, the findings decisively suggest that the PBL-HMB amalgamation significantly enhances the ownership of learning among biology students, surpassing the effectiveness of both PBL and presentations-assignment approaches.DOI: 10.17977/jps.v12i22024p058